Mathematics homework engagement and mathematics achievement among secondary school students in Sabah - Murugan, Rajoo (2017)
Malaysian students’ achievement in mathematics is lower compared to the international scores between 2003 and 2015, despite spending a large amount of time on mathematics homework (TIMSS, 2015). Previous studies have identified Mathematics homework engagement (MHE) as the most important factor to predict mathematics achievement. This study is aimed to determine the time spent and average mathematics homework done weekly, besides identifying the MHE factors (students’, teachers’, parents’ & school managements) that contribute towards mathematics achievement. The study is also intended to determine whether time spent on mathematics homework moderates the relationship between students’ MHE and mathematics achievement. Here, quantitative and qualitative approaches are used, including questionnaires, interviews and content analysis. Stratified random sampling was used to select 415 Form Four students from secondary schools from four zones in Sabah, Malaysia. To assess the MHE, 22 items, developed from the literature review, were used. The mathematics achievement was measured using the 2015 mid-year mathematics test set by the Sabah Education Department. The MHE involved 15 mathematics teachers and 15 students who went through semi-structured interviews. The findings showed students spent 60 to 120 minutes weekly on 10 mathematics questions on average, comprising low, medium and high level. All MHE factors, except for parents’, were significant towards mathematics achievement. Furthermore, time spent on mathematics homework moderates the relationship between students’ mathematics engagement and mathematics achievement. Interviews revealed that, for effectiveness, mathematics teachers’ assigned homework based on students’ ability, marked and gave encouraging comments, which resulted in better mathematics achievement. The findings of this study is a guideline for mathematics teachers to adapt the existing practice of doing homework to be more practical and relevant, especially those teaching Form Four students in order to improve mathematics achievement at all levels.